Evaluation of long‐term biocompatibility and capsular bag opacification with a new silicone–polyimide plate‐type intraocular lens in the rabbit model. Issue 7 (July 2016) - Li, Jack; Werner, Liliana; Guan, Jun J.; Reiter, Nicholas; Mamalis, Nick
Abstract : Purpose : To evaluate the long‐term biocompatibility and safety of the new SC9 intraocular lens (IOL) after implantation in rabbit eyes, in accordance with the requirements of the International Organization for Standardization 11979‐5, Annex G:2006(E). Setting : John A. Moran Eye Center, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Bilateral phacoemulsification was performed on 9 New Zealand white rabbits; 1 eye received the test IOL and the contralateral eye received a commercially available plate‐type silicone control IOL (AA4204VL). Two rabbits were humanely killed at 2 months and the remaining at 6 months. After gross examination of the eyes from the posterior Miyake‐Apple view, select IOLs were explanted and had surface staining for implant cytology. All globes were then sectioned and processed for complete histopathologic examination. Results : Overall uveal biocompatibility was similar between the test IOLs and control IOLs throughout the study. The mean posterior capsule opacification at 6 months was 0.8 ± 0.27 (SD) in the test group and 4.0 ± 0 in the control group ( P = .001, t test: paired 2‐sample for means). The mean posterior synechiae formation at 6 months was 1.28 ± 1.25 in the test group and 2.71 ± 0.75 in the control group ( P = .01). A histopathologic examination confirmed the relative lack of capsule opacification in the study eyes compared with the control eyes and the absence of untoward inflammatory reaction or toxicity in all eyes. Conclusion : The new IOL maintained an open capsular bag secondary to its design, which appeared to prevent overall capsular bag opacification and retain uveal and capsule biocompatibility. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.